Effect of Early Solid Food Feeding and the Absence of Colostrum Feeding on Neonatal Mortality and Its Possible Intervention Strategy - Hananto Wiryo (Indonesian Pediatric Society, 1999)
The provision of banana as early solid food feeding together with the absenceof colostrum feeding in neonates proven to be the cause of symptoms of intestinalobstruction (SlO). More than 64% of mothers in West Nusa Tenggara (WNT) and76% in East Java (EJ) fed their newborn babies with chewed banana and 83% ofthose in WNT and 78% in EJ had a custom of discarding their colostrum. We suggest the same condition in other provinces in Indonesia; 8.49% neonates died with the sign of SIO (see 1), and 23.07% died of diarrhea. Totally, more than 30% of neonatal mortality is cause by banana as early solid food feeding and the absence of colostrum feeding. The application of the health intervention module was proven to be very effective in reducing the custom of provision of banana as early feeding. Therefore, the application of the health intervention module, as a model, based on a previousethnographic study, and spreading the message community by formal and informalleader with their active organization, is an appropriate method that can be applied toeliminate disadvantageous custom in a corrununity in a relatively short period of time.